The Effect of Training Problem-Solving on Maladapted Behavior of Pre-School Children - Farid Marandi, Behrouz; Kakabaraee, Keivan; Hosseini, Saeede sadat (Iranian Journal of Educational Sociology, 2022)
Purpose: The purpose of this study was to investigate the effect of problem solving on preschool children 's maladaptive behavior. Methodology: The method of this study was practical and quasi-experimental with pretest-posttest design with control group. The statistical population of this study was preschool children of Kermanshah kindergartens. Twenty-four of these eligible volunteer children were selected using available sampling method and were assigned to experimental and control groups. Gresham & Elliott (1990) Social Skills Rating Scale was used to collect the data. Pre-test was administered to both groups, then the experimental group received 16 sessions of problem-solving skills training Intervention sessions were held 3 times a week with the presence of a trainer and an assistant for 45 minutes. The control group did not receive targeted intervention. Then, post-test was performed on both groups. After four months, follow-up tests were performed for both groups to evaluate the reliability of the results over time. Data analysis was performed using multivariate analysis of covariance at the significant level 0.05 and Spss24 software. Findings: The results showed that there was a significant difference between preschool children in maladaptive behavior (internal and external behavior) (P